Fortællingens dynamiske arkiv : Fortælleformer og narrativt begær i SKAM - Veel, Kristin (Nordisk Tidsskrift for Informationsvidenskab og Kulturformidling, 2017)
With a starting point in the success that the netdrama series SKAM has had in engaging its audience in an almost addictive relation, this article examines how the series makes use of formal techniques such as repetition, intermissions and a minute-by-minute temporality to generate what may be considered a “narrative desire”, with a classic term borrowed from literary scholar Peter Brooks. I here argue that the mode of narration that arises from the amorphous, transmedial and fan-engaging universe that is SKAM, resonates with the characteristics of the dynamic, digital archive and the particular spatial and temporal configuration, which the possibilities of digital technology create for production, storage, distribution and consumption of text, sound and images.